From mao to market : - Wedeman, Andrew Hall (Cambridge University Press, 2003)
Andrew Wedeman argues that economic reform in China succeeded because government failed to prevent local officials from forcing prices to market levels. Reformers opted for a hybrid system of price controls in the 1980s, wherein commodities had both fixed and floating prices. Depressed fixed prices led to "resource wars," as localities vied for control over undervalued commodities while inflated prices fueled an investment boom that saturated markets and led to import barriers. Although local rent seeking and protectionism appeared to carve up the economy, they had actually cleared the way for sweeping reforms.